Global Alliance on Climate-Smart Agriculture: Action Group on Knowledge - CGIAR Research Program on Climate Change, Agriculture and Food Security; Food and Agriculture Organization of the United Nations (Food and Agriculture Organization of the United Nations, 2014)
Since 2010 Climate-Smart Agriculture (CSA) has become an increasingly accepted approach, with many governments, civil society organisations, farmers and businesses interested in implementing CSA programmes. In September 2014 an Alliance on Climate-Smart Agriculture will be launched to provide a mechanism to coordinate and support the global adoption of CSA. Three Action Groups have been formed: Knowledge, Investment and Enabling Environment. The Alliance's Action Group on Knowledge: is co-led by UNFAO and CGIAR/CCAFS. The group aims to identify the major knowledge priorities, key areas of work and knowledge products needed to facilitate the successful adoption and upscaling of CSA.